Benefits of Oketani Massage to Solve Breast Milk Problems: A Scoping Review - Dary, Sri Wulan; Sulistyaningsih, Sulistyaningsih (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Many problems arose during the puerperium, including the production of little breast milk, milk that was not smooth, and the dam of breast milk. The hormones prolactin and oxytocin secretion impact how well breast milk is produced. The mother's mental health impacts how these two hormones are secreted. When a mother is under psychological strain (stress), the hypothalamus's work function is suppressed, preventing the pituitary gland from secreting prolactin and oxytocin. This study aimed to find the latest scientific evidence on the benefits of Oketani massage to overcome breast milk problems. The PICO Framework and PRISMA-ScR Checklist were used in this scoping review. The literature search in this study used 4 databases: Pubmed, Science Direct, Research Rabbit, and ResearchGate. The research used the Joana Briggs Institute (JBI) Appraisal Tool. There are 392 potentially relevant articles, and 11 eligible articles were selected. Article inclusion criteria were articles published in 2017–2023 in English or Indonesian, and articles focused on Oketani massage to address breastfeeding problems, namely the smoothness of breast milk, milk production, and milk dam. These 11 articles explain and prove scientifically that the Oketani massage technique and the Oketani massage combination will affect milk production, smooth milk, and breast milk dam. There is a conclusion that Oketani Massage can be used to overcome breast milk problems in postpartum mothers. Oketani massage can be done with 8 manual massage techniques and lasts 30-45 minutes, i.e., 15-20 minutes each for each breast.  And also, health workers are advised to learn Oketani massage techniques as a therapy to overcome breast milk problems, which is expected to overcome breast milk problems.